PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2019-2021 - Ibrahim, Ahmad Dzaky; Andayani, Wuryan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Profitability exhibits company management’s efficiency and effectiveness in utilizing assets and managing its operational activities. This study aims to test and provide empirical evidence of the effect of corporate social responsibility disclosure, firm size, and leverage on the profitability of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019, 2020 and 2021. Involving the sample of 15 companies selected through purposive sampling method with predetermined criteria. The secondary data of annual reports and sustainability reports are analyzed quantitatively by multiple linear regression utilizing IBM Statistical Package for Social Science (SPSS) software. The test results indicate that Corporate Social Responsibility disclosure and firm size have no effect on profitability while leverage has a negative effect on profitability.